Giant and irregular pituitary neuroendocrine tumors surgery: comparison of simultaneous combined endoscopic endonasal and transcranial and purely endoscopic endonasal surgery at a single center - Jun Fu; Wenwei Luo; Chunlin Zhang; Zhicheng Wang; Wenjian Fan; Yuanxiang Lin; Dezhi Kang; Jianping Song; Changzhen Jiang; Xiaorong Yan (Chinese Neurosurgical Journal)
Abstract Background Surgical management of giant and irregular pituitary neuroendocrine tumors (GIPitNETs) presents a significant challenge in neurosurgery. While endoscopic endonasal surgery (EES) is a widely used approach for PitNETs, GIPitNETs with extensive intracranial extension pose challenges for purely EES. We use simultaneous combined endoscopic endonasal and transcranial surgery (CECS) for the treatment of this type of tumor. Currently, there is limited research comparing CECS to EES for GIPitNETs. This study aims to compare the efficacy and short outcome of CECS and purely EES in the management of GIPitNETs to better understand the advantages and limitations of each surgical approach. Methods The data of GIPitNETs patients who underwent surgery between March 2018 and May 2023 at a single center were retrospectively reviewed. All included cases were divided into CECS and EES groups according to the treatment modality received. The baseline characteristics and tumor imaging features of patients were compared between the groups, as well as surgical results, perioperative complications, and last follow-up outcomes. Results A total of 50 patients met the inclusion criteria, with 27 undergoing CECS and 23 EES. CECS achieved a significantly higher GTR rate compared to EES (66.7% vs. 13.0%, p < 0.0001). CECS had longer operation times and hospital stays, but both approaches had similar rates of complications, including intracranial infection, CSF leakage, new pituitary dysfunction, postoperative diabetes insipidus, and vascular infarction. CECS reduces the risk of postoperative bleeding. Tumor recurrence and reoperation were significantly more common in the EES group. Conclusions CECS is a safe and effective surgical approach for GIPitNETs, leading to higher rates of GTR, comparable complication rates, and reduced risk of postoperative bleeding when compared to purely EES. EES was associated with more tumor recurrence. Further long-term follow-up data is needed to validate these findings.